A arte naïf de Militão dos Santos: uma aproximação etnográfica - Rufino, Joseane Maria de Araújo (2015)
The present work searches for an ethnographic approach to the artistic universe of Militão dos Santos, who was born in Caruaru/PE and now lives in Recife/PE, Brazil. Taking the specificity of the artistic Naïf expression into account, we start presenting theoretical reflections about this kind of art and its characteristics. Although, our major concern is that the sociocultural aspects showed in his works as well as his life story and artistic formation. Dealing with such elements from the point of view of an anthropological method based on the concept of “ethnobiography”, we propose a symbolic analysis of a set of representative paintings. Having this in mind, we try to observe the relationship between cultural regional themes, subjectivity and creativity in the artist’s works. In accordance with related experiences, like his deafness caused in childhood and lonely life in Rio de Janeiro, we draw the conclusion that these events are present in his paintings not in a dramatic way but in a playful, oneiric and lively ones found in his themes.